EFEK MODEL PEMBELAJARAN INQUIRY TRAINING BERBASIS MEDIA KOMPUTER TERHADAP KETERAMPILAN PROSES SAINS DAN KEMAMPUAN BERPIKIR KRITIS SISWA - Andar M. Hutagalung (Jurnal Pendidikan Fisika, 2013)
The purpose of the research is to know if there is any difference between the skill of students in a science process and the students critically thinking ability using inquiry training’s model of computer base. The method used in the research is quasi experiment or consisting two variables (classes),one class used as an experiment and one as a control class. The result shownthat skill of students in a science process are N-gain experiment class 0.84(high category) and control class 0.68 (medium category). On the contrarybased on the students critically thinking ability of N-gain experiment class0.75 (high category) and control class 0.67 (medium category). Therefore inquiry training’s model of computer base significantly give a better outcomethan inquiry training’s model.